2011
DOI: 10.4103/0019-5154.77549
|View full text |Cite
|
Sign up to set email alerts
|

Decreased effect of glucantime in cutaneous leishmaniasis complicated with secondary bacterial infection

Abstract: Background:Glucantime is regarded as the first-line treatment of cutaneous leishmaniasis (CL); however, failure to treatment is a problem in many cases.Aim:The aim was to evaluate the therapeutic effect of glucantime in CL complicated with secondary bacterial infection compared to uncomplicated lesions.Methods:This experimental study was performed in Skin Diseases and Leishmaniasis Research Center, Isfahan, Iran. A total of 161 patients enrolled in the study had CL confirmed by positive smear of lesions. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 6 publications
2
14
0
1
Order By: Relevance
“…Interestingly, the different topological sites of our samples did not show any differences in the skin microbiota, although we only had a few samples from moist and sebaceous sites. Yet comparable to what has been reported by culture dependent and independent methods (Isaac-Marquez and Lezama-Davila, 2003; Sadeghian et al, 2011; Layegh et al, 2015; Salgado et al, 2016), our results demonstrated that Staphylococcus aureus and an unclassified species of Streptococcus are highly abundant on lesional skin. This dysbiosis was also present on skin sites adjacent to the lesion.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the different topological sites of our samples did not show any differences in the skin microbiota, although we only had a few samples from moist and sebaceous sites. Yet comparable to what has been reported by culture dependent and independent methods (Isaac-Marquez and Lezama-Davila, 2003; Sadeghian et al, 2011; Layegh et al, 2015; Salgado et al, 2016), our results demonstrated that Staphylococcus aureus and an unclassified species of Streptococcus are highly abundant on lesional skin. This dysbiosis was also present on skin sites adjacent to the lesion.…”
Section: Discussionsupporting
confidence: 91%
“…The presence of bacterial secondary infection may cause local pain and produce serous and purulent exudate that completely or partially recovers the ulcer and subsequently dries into crusts ( MS 2017 ), and it may interfere with the healing process ( Navarro et al 2009 , Sadeghian et al 2011 ).…”
mentioning
confidence: 99%
“…The incidence of secondary infection in CL lesions ranges from 23.6-81% ( Vera et al 2001 , Gonçalves et al 2009 , Sadeghian et al 2011 ). The most frequently isolated bacteria from cutaneous lesions of leishmaniasis are Staphylococcus aureus , Staphylococcus epidermidis , Pseudomonas aeruginosa , Klebsiella pneumoniae and Corynebacterium diphtheriae ( Vera et al 2001 , Gonçalves et al 2009 , Navarro et al 2009 , Sadeghian et al 2011 ).…”
mentioning
confidence: 99%
“…In the majority of randomized controlled clinical trials (RCTs) in which the efficacy of different therapeutic interventions for acute Old World cutaneous leishmaniasis have assessed, principles of wound management has been ignored [12], [13]. Sadeghian et al have reported a decrease in the therapeutic efficacy of i.l.MA injections in CL lesions with secondary bacterial infection [14]. It has been recommended to use moisturizing dressings (polyurethane containing types) in the treatment of the lesions of CL [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been recommended to use moisturizing dressings (polyurethane containing types) in the treatment of the lesions of CL [15]. Almost all chronic wounds are colonized with different microorganisms and it is well known that when the bacterial burden of the wound gradually increases, it could interfere with normal wound healing, deteriorate the inflammation and pain of the wound, and results in more complex management of it [12]–[14].…”
Section: Introductionmentioning
confidence: 99%